2007
DOI: 10.1097/mlg.0b013e31802f4154
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation for Tinnitus: A Pilot Study

Abstract: rTMS is a promising treatment modality that can transiently diminish tinnitus in some individuals, but further trials are needed to determine the optimal techniques required to achieve a lasting response. It is unclear whether the improved reaction times were caused by tinnitus reduction or a general effect of rTMS. PET/CT scans immediately after treatment suggest that improvement may be related to reduction of cortical asymmetry associated with tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 13 publications
8
72
2
Order By: Relevance
“…The results confirmed the theory about the auditory cortex asymmetry published in different articles [3][4][5][6][7] and the hyperactivation of the primary and secondary auditory cortex on the left side (the patient is right handed). This is the opposite side of the tinnitus.…”
Section: Acquisition Proceduressupporting
confidence: 80%
“…The results confirmed the theory about the auditory cortex asymmetry published in different articles [3][4][5][6][7] and the hyperactivation of the primary and secondary auditory cortex on the left side (the patient is right handed). This is the opposite side of the tinnitus.…”
Section: Acquisition Proceduressupporting
confidence: 80%
“…In this trial, patients were treated with 1-Hz rTMS because this was thought to lead to suppression of neural activity [Hallett, 2007] and thus suppression of hyperactivity underlying tinnitus. Other parameters for rTMS set-up were chosen in line with most previous studies to aid comparability: patients were treated on 110% of their motor threshold with a figure-of-eight coil [Kleinjung et al, 2005Langguth et al, 2007;Smith et al, 2007]. The handle of the coil pointed upwards [Kleinjung et al, 2005Langguth et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed an improvement for both rTMS and placebo but did not compare the groups with each other [Anders et al, 2010]. The last Rossi [2007] 16 left TP VAS (0-100) -20 (67→47) -7 (67→60) significant effect Smith [2007] 4 most active PAC on PET TSIQ VAS (0-100)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also reported that Grapergiesser initially suppressed tinnitus by transcutaneous electrical stimulation using Volta's Platinum-Zinc cell 4 . In fact, one of the outstanding features of this phantom sound is that it can be inhibited by auditory external stimuli such as acoustical, electrical, and magnetic fields [5][6][7][8] . It is obvious that following the offset of appropriate masking stimuli, tinnitus may remain suppressed for a short period of time.…”
Section: Introductionmentioning
confidence: 99%